2008
DOI: 10.1109/tkde.2007.190647
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Remote Data Possession Checking in Critical Information Infrastructures

Abstract: Checking data possession in networked information systems such as those related to critical infrastructures (power facilities, airports, data vaults, defense systems, and so forth) is a matter of crucial importance. Remote data possession checking protocols permit checking that a remote server can access an uncorrupted file in such a way that the verifier does not need to know beforehand the entire file that is being verified. Unfortunately, current protocols only allow a limited number of successive verificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
120
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 250 publications
(120 citation statements)
references
References 5 publications
0
120
0
Order By: Relevance
“…To circumvent the problem of exponentiating the entire file, Sebé et al [11] presented a scheme to remotely verify data integrity by first fragmenting the file into blocks, fingerprinting each file block, and then using an RSA-based hash function on the blocks. Thus, the data file F is divided into a set of m blocks: F = {b 1 , b 2 , .…”
Section: Provable Static Data Possessionmentioning
confidence: 99%
See 1 more Smart Citation
“…To circumvent the problem of exponentiating the entire file, Sebé et al [11] presented a scheme to remotely verify data integrity by first fragmenting the file into blocks, fingerprinting each file block, and then using an RSA-based hash function on the blocks. Thus, the data file F is divided into a set of m blocks: F = {b 1 , b 2 , .…”
Section: Provable Static Data Possessionmentioning
confidence: 99%
“…Their scheme does not require the exponentiation of the entire file. Figure 4 demonstrates the protocol of Sebé et al [11].…”
Section: Provable Static Data Possessionmentioning
confidence: 99%
“…Their construction is based on Sebé et al's protocol [24] and the homomorphic verifiable tag technique due to Ateniese et al [6]. While it can be shown that the challenge-response protocol "does not leak any information of the data to TPA", it does not prevent the verifier from learning information about the data from the meta-data.…”
Section: Analysis Of Hao Et Al's Rdic Protocolmentioning
confidence: 99%
“…Sebé et al [24] proposed a data possession checking protocol which achieves many desirable properties such as unlimited number of verifications, low communication cost, blockless verification, and security against a malicious server. However, this scheme does not support public verifiability nor guarantees data privacy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation